APPLICATION OF WET CUPPERATION TO REDUCE THE SCALE OF SHOULDER PAIN IN MYALGIA TRAPEZIUS PATIENTS - Lukman; Nurna Ningsih; Firman Nugraha Putra (Pusat Riset dan Inovasi Nasional, 2022)
Background : Muscle pain or it can also be called myalgia is one of many disorders and diseases in the body. In general, myalgia is caused by misuse of muscles or muscles that are too tense. Several nursing action therapies for joint pain management using non-pharmacological therapy, one of which is Cupping Therapy, Research Objectives: The results of the application of the wet cupping technique to reduce the pain scale in the shoulder with Trapezius Myalgia in the work area of the Sidorejo Health Center 2022., Research Methods: The Type of This research is descriptive by using the case method. The study was conducted in April 2022. The subjects in this case study were two clients with a diagnosis of Trapezius Myalgia who met the inclusion and exclusion criteria. Research Results: After cupping therapy was performed for 1 time in 2 weeks, the results showed that the pain scale in the subjects decreased in Subject I from pain scale 5 (moderate pain) to pain scale 2 (mild pain) and in subject II there was a decrease in pain scale from pain scale 6 (moderate pain) to pain scale 3 (mild pain). Conclusion: The implementation of cupping therapy can reduce the pain scale in patients with Trapezius myalgia according to the subject's condition and lifestyle factors in each subject in the working area of the Sidorejo Health Center, Lubuklinggau City.